OMEDIG : Rancang Bangun Oksigen Meter Digital Berbasis IoT untuk Fasilitas Kesehatan Masyarakat - Firdaus Firdaus; Zainullah Muhamad; Mahabito Saka Nusantara (UII, 2020)
The problem raised in this final project is the need for a technology that can measure the oxygen flow rate with precision, and can record the total volume of oxygen used to overcome the problem of oxygen pricing in health facilities. This is because health facilities generally only use the duration of oxygen consumption and multiply it by the flowrate as the basis for pricing oxygen to patients. The suggestion of this tool is that patients and health facilities alike know the total volume of oxygen that has been used. In system design, there are several changes from the proposals that have been made previously. This is done because the specifications of the tool do not match which can reduce the performance of the tool itself. The changes made were to replace the single head regulator into a regulator that is already circulating in general and the addition of a fan component as a cooler in the control system of the digital oxygen meter. At the implementation stage, the first thing to do is testing the SFM4100 sensor and testing the serial communication of the Arduino WiFi microcontroller. Furthermore, the overall tool testing and tool testing on the Thinger.io user interface is carried out to find out how well it records data. Based on the results of the tests carried out, OMEDIG has an error of Â± 1.82% in reading the oxygen flowrate. This means that OMEDIG has a very good accuracy rate of Â± 98.18%, with the ability to measure oxygen flowrates up to 10 LPM. Realtime data transmission on Thinger.io every 1 second and data will be stored in the database every 1 minute. Data from the database can be downloaded in the form of an excel file so that it will be easier for health facilities in the process of determining oxygen rates used by patients. The impact of the implementation of this tool can provide alternative solutions for health facilities to be more fair and transparent in determining oxygen tariffs. In addition, it can also facilitate the work of medical personnel in terms of adjusting the oxygen flowrate (using a keypad) and also allows doctors to monitor (remotely) the amount of oxygen flowrate given by medical personnel is in accordance with what was ordered. The most important thing is that the health facility and the patient can find out the flowrate and the total volume of oxygen used through the LCD display on the device. So that patients can estimate the costs that must be incurred for the use of oxygen. And also health facilities no longer determine oxygen rates based on duration of use, but based on the total volume of oxygen that has been used by patients